Municipal solid waste management in the district of Huacrachuco-Marañón. A proposal for improvement - Campos-Huayanay, Charles J. (2019)
The objective of the investigation, to evaluate the management and management of municipal waste in the district of Huacrachuco, province of Marañón, Department of Huánuco and from which to propose a proposal for improvement. Methods. The study was quantitative, applied, descriptive, transversal and prospective. The sample consisted of 80 heads of family / housing, 2 public institutions, 2 educational centers and 4 commercial establishments. The data is collected in an interview guide, in an observation sheet and in a checklist, obtained from the Municipal Registry of the 2017 period; applying ethical criticism. Descriptive analysis was performed and the hypothesis was checked by component weighting. Results. The per capita production of solid waste was 0.30 kg / hab / day, 1.00 t / day, 30.00 t / month and 365,000 t / year; predominantly organic waste in 45.36% and sanitary waste in 12.00%. With respect to the evaluation of solid waste management and management in the Municipality of Huacrachuco, a score of 20.0 / 100 was obtained, a minimum value with respect to the departmental evaluation. Conclusion. municipal solid waste management in the district of Huacrachuco is at a low level with respect to the reference, departmental and national value.